A review of hydro-meteorological hazard, vulnerability, and risk assessment frameworks and indicators in the context of nature-based solutions. (November 2020) - Shah, Mohammad Aminur Rahman; Renaud, Fabrice G.; Anderson, Carl C.; Wild, Annie; Domeneghetti, Alessio; Polderman, Annemarie; Votsis, Athanasios; Pulvirenti, Beatrice; Basu, Bidroha; Thomson, Craig; Panga, Depy; Pouta, Eija; et al.
Abstract: Nature-based solutions (NBS) are increasingly being implemented as suitable approaches for reducing vulnerability and risk of social-ecological systems (SES) to hydro-meteorological hazards. Understanding vulnerability and risk of SES is crucial in order to design and implement NBS projects appropriately. A systematic literature review was carried out to examine the suitability of, or gaps in, existing frameworks for vulnerability and risk assessment of SES to hydro-meteorological hazards. The review confirms that very few frameworks have been developed in the context of NBS. Most of the frameworks have emphasised social systems over ecological systems. Furthermore, they have not explicitly considered the temporal dimension of risk reduction measures. The study proposes an indicator-based vulnerability and risk assessment framework in the context of NBS (VR-NBS) that addresses both the above limitations and considers established NBS principles. The framework aims to allow for a better consideration of the multiple benefits afforded by NBS and which impact all the dimensions of risk. A list of 135 indicators is identified through literature review and surveys in NBS project sites. This list is composed of indicators representing the social sub-system (61% of total indicators) and the ecological sub-system (39% of total indicators). The list will act as a reference indicator library in the context of NBS projects and will be regularly updated as lessons are learnt. While the proposed VR-NBS framework is developed considering hydro-meteorological hazards and NBS, it can be adapted for other natural hazards and different types of risk reduction measures. Highlights: Assessing social-ecological risks to natural hazards is crucial for NBS projects. Existing risk assessment frameworks have not been developed in the context of NBS. Social and ecological aspects are not equally addressed in existing frameworks. A vulnerability and risk assessment framework in the context of NBS is proposed. 135 social-ecological indicators are provided as a reference for risk assessment.